Vladimir Jabotinsky's Story of My Life - Jabotinsky, Vladimir, 1880-1940 (Book collections on Project MUSE., 2016)
Vladimir Jabotinsky is well remembered as a militant leader and father of the right-wing Revisionist Zionist movement, but he was also a Russian-Jewish intellectual, talented fiction writer, journalist, playwright, and translator of poetry into Russian and Hebrew. His autobiography gives a more nuanced picture of Jabotinsky than his popular image, but it was never published in English. Here, editors Brian Horowitz and Leonid Katsis present this much-needed translation, based on a rough draft of an English version that was discovered in Jabotinsky's archive at the Jabotinsky Institute in Tel Aviv.